Connecting the global H-mode power threshold to the local radial electric field at ASDEX Upgrade. (12th May 2020) - Cavedon, M.; Birkenmeier, G.; Pütterich, T.; Ryter, F.; Viezzer, E.; Wolfrum, E.; Dux, R.; Happel, T.; Hennequin, P.; Plank, U.; Stroth, U.; Willensdorfer, M.
Abstract: The relation between the macroscopic input power required at ASDEX Upgrade to access the H-mode P t h r and the microscopic E × B shear has been investigated via fast charge-exchange recombination spectroscopy (CXRS) measurements at various toroidal magnetic fields, different electron densities, and in both hydrogen and deuterium plasmas. For the H-mode onset, a threshold in the v E × B minimum, an approximation of the E × B shear, has been found. This identifies v E × B and not E r as the important player for the L-H transition. A database of measurements including CXRS, Doppler reflectometry measurements and comparison to neoclassical approximations shows a threshold v E × B of (6.7 ± 1.0) km/s ranging over a factor of three in P t h r . Using these findings, a simple derivation of the P t h r scaling is proposed giving a physics interpretation of the B t, density and surface dependence of P t h r .